COMMUNITY SERVICE EDUCATION OF MOTHERS UNDER FIVE IN SELF-CARE, HYGIENE AND MANAGEMENT OF HEALTHY MP-BREASTS BASED ON LOCAL CULINARY IN SUB-DISTRICT THE FIELD - Dwi Ris Hasanah; Suriati Lubis; Yulia Amelia (Jurnal Masyarakat Indonesia (Jumas), 2025)
Hygiene food management, the fulfillment of proper and quality complementary foods after the child is six months old is a crucial challenge because breast milk alone is no longer sufficient for the increasing nutritional needs. Therefore, mothers under five must have comprehensive knowledge in processing and presenting healthy, balanced, and safe MP-ASI. A weak understanding of the texture, frequency, and diversity of food is at high risk of causing children to experience malnutrition, such as underweight and stunting. The program will be carried out on April 24, 2025 through health counseling methods and demonstrations of hygiene self-care practices and the management of healthy MP-ASI based on local culinary. The results of the evaluation showed that there was an increase in understanding of knowledge and skills of mothers under five in Medan Tuntungan District in implementing family hygiene self-care and managing healthy complementary foods independently. This education is expected to utilize local food ingredients to meet children's nutritional needs to prevent the risk of malnutrition and stunting.